Pattern of maternal weight gain among primigravidae in tertiary care hospital and urban health centre - Dahake, Swati T.; Shinde, Ratnendra R. (International Journal Of Community Medicine And Public Health, 2019)
Background: The appropriate amount of weight gain during pregnancy has been a topic of interest and debate over a century. A low body mass index (BMI) and suboptimal weight gain during pregnancy are long recognised risk factors for delivery of infants too small for gestational age. Methods: The present study was observational prospective study conducted among primigravidae in two groups with sample size 197 in tertiary care hospital antenatal clinic and 97 in urban health centre antenatal clinic for the period of 1year and 6 months. Results: In tertiary care hospital average weight gain was 10.04 kg with 33 (16.75%) women gained less than or equal to 8 kg weight gain, 148 (75.13%) gained weight in range of 8.1 to 16 kg while 16 (8.12) gained more than 15 kg weight during pregnancy while In urban health centre average weight gain was 8.96 kg with 46 (47.42%) women gained less than or equal to 8 kg weight gain, 45 (46.39%) gained weight in range of 8.1 to 16 kg while 6 (6.19%) gained more than 16 kg weight during pregnancy. Women with lower BMI found to gain lesser weight compared to normal body mass women. Conclusions: Presence of low BMI was an add on social risk factor which may adversely impact the weight gain in the mother and expected child.